Novel fiber bragg grating sensing method based on the sidelobe modulation for ultrasound detection - Liang, Sheng (2020)
This contribution demonstrates the interaction between the fiber Bragg grating (FBG) and the ultrasound. When the grating length is much longer than the ultrasonic wavelength, the conventional wavelength-modulation method is invalid. In order to find out an effective sensing method, in this case, a novel sidelobe modulation has been proposed and investigated. When grating length is much longer than the ultrasonic wavelength, the Bragg wavelength is not shifted; however, the reflectivity of sidelobe is modulated by ultrasound, periodically, which can be utilized as an effective ultrasound sensing method. In order to optimize the performances of this method, the characteristics of the sidelobes are further analyzed for different ultrasonic displacement amplitude, frequency, and grating length, respectively. The analysis results indicate that a proper choice of the grating length would enable the sidelobe modulation to be utilized for detecting the ultrasound with an appropriate range of ultrasonic frequency and amplitude. This method is preliminarily validated in the experiment, and the experimental results show that our proposed sidelobe-modulation method is effective to detect the 7.8 MHz ultrasonic wave by a simple intensity-demodulation using a 5 mm FBG, where the wavelength modulation is invalid.